SOSIODEMOGRAPHIC DETERMINANTS OF HEALTH FACILITY UTILIZATION IN INDONESIA: Determinan Sosiodemografi Utilisasi Pelayanan Kesehatan di Indonesia - Rahayu, Eka Putri; Ariyanti, Rea; Rahayu, Agustin Putri (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2025)
Background: Health service facility utilization is crucial for determining healthcare service success and accessibility. Sociodemographic factors significantly influence utilization patterns. Aims: This research aims to examine the relationship between sociodemographic factors and health facility utilization patterns among the Indonesian population Methods: Secondary data from the 2023 Indonesian Health Survey (Health Development Policy Agency, Ministry of Health) were analyzed using a quantitative cross-sectional approach. Chi-square tests and binary logistic regression were employed for bivariate and multivariate analyses Results: Non-JKN health insurance was the dominant factor with PR = 2.4 (95%CI PR: 2.335-2.645), followed by never in union with PR= 1.328 (95%CI PR:1.269-1.390). Married with PR= 1.3 (95%CI PR: 1.224-1.381), unemployed with PR= 1.262 (95%CI PR: 1.226-1.300), children with PR= 1.181 (95%CI PR: 1.110-1.257), men with PR =1.030 (95% CI PR: 1.005-1.005). Factors reducing utilization likelihood included are rural residence with PR= 0.378 (95%CI PR: 0.368-0.388), secondary education with PR= 0.390 (95%CI PR: 0.376-0.404), adult with PR= 0.650 (95%CI PR: 0.603-0.701), primary education with PR= 0.703 (95%CI PR: 0.684-0.722), non formal occupation with PR= 0.955 (95%CI PR: 0.922-0.989). Conclusion: The binary logistics regression shows that health insurance ownership is the most dominant predictor, with individuals holding non-JKN health insurance being 2.4 times more likely to utilize healthcare services compared to those with JKN insurance. Therefore, geographical disparities and educational levels are critical obstacles that require intervention in efforts to improve access to health services. Keywords: Determinants, Health Facility, Sociodemographic, Utilization, SKI 2023